STUDI PENGELOLAAN ADMINISTRASI BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH KEJURUAN NEGERI 5 PONTIANAK TAHUN 2019 - Ningsih, Retna Wahyu; Asrori, M; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe existence of good administration and management will greatly support the guidance and counseling programs that exist in schools. Administration includes all activities that are planned and carried out regularly to achieve the educational goals outlined. The administration intended in this study includes studentsbiodata, observation guidelines, anecdotal record, student call formats, and home visit record formats. The general problem of this research is How is the administration and guidance counseling management study of SMK Negeri 5 Pontianak in 2019?. In this research, the method used is descriptive method. The form of research used was a survey. Data collection tools used are documentation studies and interviews. The results of the study stated that in the administration of guidance and counseling administration, the aspects studied were in the form of studentsbiodata, observation guidelines, anecdotal record, student call formats, and format of home visit records of SMK Negeri 5 Pontianak in 2019 as a whole as complete as it meant in how to make, use, evaluate criteria and evaluate every aspect of the administration of guidance and counseling has been going very well.Keywords: management administration, vocational high school administration.